(untitled) (Journal of Preventive and Social Medicine, 2021)
Introduction: Although Tuberculosis mostly affects lungs in about 85% cases, but can cause lesion almost in every part of the body. Extrapulmonary TB (EPTB) accounts for 15 to 20% which involves other parts of the body beside the lungs. There are several methods that can diagnose Pulmonary TB (PTB) conclusively , but extrapulmonary TB is very difficult to diagnose till now especially in resource limited settings. Though it is not communicable but diagnostic delay has made it significant cause of morbidity and mortality. The snidy was aimed to find out the Gene Xpert as one of the diagnostic tool for EPTB. Methods: A laboratory based descriptive cross sectional study was conducted over a period of 17 months from January 2017 to May 2018 to ascertain the performance of Gene Xpert technique as a diagnostic tool for EPTB. Data were collected through checklist and a total of 77 clinical samples were collected purposively with prior infom,ed consent from suspected EPTB patients following ethical issues. Laboratory investigations were perfomed at Rhodolphe Merieux Laboratory, Chittagong, Bangladesh with Gene Xpert MTB/Ri f assay, conventional culture (LJ media) and Microscopy (ZN stain) for the presence of Mycobacteium tuberculosis (MTB). Results: Among the 77 samples from suspected cases, seven(9.09%) from CSF, one(!.29%) from pus and one(l .29%) from lymphnode specimens were positive by Gene Xpert MTB/Rif assay.Only one(1.29%) CSF specimen was found to be culture and microscopy positive which was Gene Xpert positive also. Except one specimen from pus that is both Gene Xpert and microscopy positive but culture negative, no other specimens from EPTB cases were culture and microscopy positive. Conclusion: Diagnosis of EPTB is challenging in worldwide. As it is paucibacillary, routine diagnostic test in detecting MTB is difficult. Gene X pert showed promising outcome in early detection of life threatening EPTB cases like TB meningitis which is common in developing countries. JOPSOM 2020; 39(1): 26-30